Effect of Costus Specious Extract on Some Types of Pathogenic Bacteria - Hanan Shihab Ahmad (Journal of Global Pharma Technology, 2019)
The present study aimed to investigate the effect of different concentrations of cold water extract, hot water extract, and alcohol extract of Costus specious plant with concentrations of 25, 50, 100, 150, 200, 250, 300, 350 micro liters / ml tested on eight pathogenic bacteria Staphylococcus aureus, Proteus Klebsiella Bacillus, Entrobactera, Serratia Pseudomonas aeruginosa Escherichia coli, Was obtained from the laboratories of the hospital of the city of medicine in Baghdad. The method of spread across the cattle. There was an effect on the bacteria at different concentrations in the cold water extract Costus specious where there is no effect of the extract on the bacteria enterobacteria. The results of the measurement of the diameter of the inhibition are clear. There is an effect on the bacteria species with the hot water extract of the Indian variety with different concentrations and the alcoholic extract of the Costus specious plant which had an effect on the bacteria species with different concentrations. The difference in the effect of the extract on the growth of the bacteria depends on the type of bacteria and concentration of the extract The effect of cold water extract at a concentration of 5 g / mL was more effective on Staphylococcus aureus. The effect of the hot water extract at a concentration of 5 g / 3 ml had an effect on Klebsiella and E. coli bacteria. The alcohol extract had the highest effect of 2 g / 5 ml on E. coli and the 5 g / mL alcohol extract was more effective on Serratia and Enterobacteria and no effect on bacteria Klebsiella.